Maqashid Sharia Analysis of Insurance Implementation in Sharia Pawnshops - Peranginangin, Siska Junianti; Sudiarti, Sri; Syarbaini, Ahmad Muhaisin B (Iqtishodia: Jurnal Ekonomi Syariah, 2024)
To control and limit self-interest in Islamic business and insurance in accordance with the commands of Allah SWT is based on Sharia, which is the foundation for Islamic commerce. Since the Maqasid Shariah approach can provide a realistic and clear picture and description of the business operations, contracts, and products in sharia pawnshops, it can be considered that the products are able to meet the needs as the times continue to evolve. Naturally, fiqh evolves rapidly over time with the aim of conforming to the maqasid of sharia to protect the welfare of society. When applying a formalistic and textual approach to fiqh, it results in gaps because there are differences. Analyzing Maqashid Syariah Insurance Implementation in Islamic Pawnshops is the purpose of this study. And by using qualitative methods. The results of the study found that the analysis of maqashid sharia insurance application in Islamic pawnshops has been implemented properly. That is, the fulfillment of Maqashid Sharia values in financing motorized vehicles on trust products that guarantee insurance in Islamic pawnshops. First, the religion of the customers is maintained. Second, the customers' souls are maintained. Third, the minds of customers and Islamic pawnshops are maintained. Fourth, the property is maintained. And finally, Fifth, the offspring is maintained.